Hernia or hernia Defect? Experimental herniology Models in Laboratory Animals - V. A. Lazarenko; I. S. Ivanov; A. A. Ushanov; E. S. Mishina; E. G. Obedkov; V. S. Kostin (Инновационная медицина Кубани, 2023)
Hernias of the anterior abdominal wall remain one of the most common surgery pathologies. There is no unified approach to modeling anterior abdominal wall hernias in the world scientific community. In order to systematize the available knowledge in this field and to contribute to the formation of a unified idea of how to create a hernia model in a laboratory animal, it seems logical to study the accumulated experience of researchers in the field of experimental herniology. We found out that hernia defects generally modeled on male laboratory rats. To understand the tissue reaction to the prosthetic material a fenestration was performed in the anterior abdominal wall (including peritoneum) except for the skin and subcutaneous fat. A replacement or prosthetic material tailored to the fenestration was sutured end-to-end into the abdominal wall. We chose laboratory rats because they are easy to take care of and cheaper than larger laboratory animals.